Idiopathic submacular hemorrhage in a young - Prashar, Sonia; Dhar, Sanjay Krishan (Indian Journal of Case Reports, 2025)
Submacular hemorrhage (SMH) is a visually devastating complication typically associated with age-related macular degeneration or other retinal vascular disorders. However, SMH can also occur in younger individuals without underlying systemic conditions. Here, we present a case of idiopathic SMH in a young, otherwise healthy patient, discussing the clinical presentation, diagnostic evaluation, management strategies, and visual outcomes. A 24-year-old male presented with painless, sudden onset of central red scotoma and gross diminution of vision in his right eye of 2 days duration. On examination, his best-corrected visual acuity was counting fingers at 2 m in the right eye and 6/6 (Snellen’s chart) in the left eye. Fundus examination of both eyes revealed myelinated nerve fibers over the superior and inferior poles of the optic disc and the right eye showing 1 disc diameter horizontally oval yellowish looking elevated lesion with red margins suggestive of SMH obscuring the fovea. Further etiological workup was within normal limits and diagnosis of right eye idiopathic SMH was made. He was managed conservatively with close follow-up and showed good visual recovery 6/6² over 8 weeks with resolution of submacular hemorrhage thus highlighting the option of observation as a management strategy in small submacular hemorrhage.